Cooling with carbon dioxide - Handagama,N; White,M; Markides,CN (Energy World, 2017)
With a growing global demand for cooling and more restrictive legislation coming into force concerning the selection of refrigerants, the refrigeration industry is looking for new alternatives. Nareshkumar Handagama, Martin White and Christos Markides discuss the role that carbon dioxide could play.